THE EFFECTS ON COMMODITY PRICES OF EXTRAORDINARY MONETARY POLICY. (18th January 2017) - AMATOV, AITBEK; DORFMAN, JEFFREY H.
Abstract: This article examines the relationship between Federal Reserve monetary policy and other macroeconomic indicators to both a broad commodity price index and an agricultural commodity price index by employing a vector error correction model. Excessive liquidity and the recent long period of ultralow interest rates appear to have played a statistically significant role in affecting prices in the commodities markets. The responses of commodity prices to monetary policy that we estimate generally conform to earlier findings, but the sensitivity of the responses appears different in the face of the unprecedented scope of recent Fed activism.